2021
DOI: 10.1136/jmedgenet-2021-107774
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac myosin binding protein-C variants in paediatric-onset hypertrophic cardiomyopathy: natural history and clinical outcomes

Abstract: BackgroundVariants in the cardiac myosin-binding protein C gene (MYBPC3) are a common cause of hypertrophic cardiomyopathy (HCM) in adults and have been associated with late-onset disease, but there are limited data on their role in paediatric-onset HCM. The objective of this study was to describe natural history and clinical outcomes in a large cohort of children with HCM and pathogenic/likely pathogenic (P/LP) MYBPC3 variants.Methods and resultsLongitudinal data from 62 consecutive patients diagnosed with HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…2 While variants in MYBPC3 were predominantly loss-of-function, there were 5 unique P/LP missense variants, and all but one were located between amino acid residues 495 to 531 within a previously reported cluster of the C3 domain. 20,21 Variants in TNNT2 and TNNI3 accounted for almost one-third of DCM and half of RCM, and while rare overall in HCM, were more likely to be associated with symptomatic presentation (P<0.01) and heart transplant or sudden cardiac death (P<0.01) when compared to P/LP variants in MYH7 and MYBPC3.…”
Section: Genetic Causes Of Cardiomyopathymentioning
confidence: 99%
“…2 While variants in MYBPC3 were predominantly loss-of-function, there were 5 unique P/LP missense variants, and all but one were located between amino acid residues 495 to 531 within a previously reported cluster of the C3 domain. 20,21 Variants in TNNT2 and TNNI3 accounted for almost one-third of DCM and half of RCM, and while rare overall in HCM, were more likely to be associated with symptomatic presentation (P<0.01) and heart transplant or sudden cardiac death (P<0.01) when compared to P/LP variants in MYH7 and MYBPC3.…”
Section: Genetic Causes Of Cardiomyopathymentioning
confidence: 99%
“…In addition, patients with disease-causing variants in MYH7 and MYBC3 were at the highest risk for developing HCM in childhood and experiencing an adverse event or requiring intervention. Indeed, while previous data had suggested that MYBPC3 variants in particular were associated with late-onset disease [38], more recent studies have shown that MYBPC3 variants in heterozygosis can cause severe phenotypic expression of disease in childhood, with a high prevalence of malignant ventricular arrhythmia [39]. Furthermore, there are data to show that, in the context of a multidisciplinary expert setting and with adequate psychological support, clinical screening of paediatric first-degree relatives does not result in psychological harm [40].…”
Section: Screening During Childhood and Adolescence For Those With An...mentioning
confidence: 99%
“…1,2 We have recently described the clinical presentation and outcomes of children with HCM caused by MYBPC3 variants and showed that these can cause early-onset disease with a high incidence of lifethreatening arrhythmias, 3 contrasting with previous suggestions that they cause late-onset disease. 4 Using the same methods, 3 we established a retrospective, longitudinal cohort of children diagnosed with HCM aged <18 years with a disease-causing variant in MYH7 at our center. Variant pathogenicity was reassessed according to the American College of Medical Genetics and Genomics criteria.…”
mentioning
confidence: 92%
“…Hypertrophic cardiomyopathy (HCM) presenting in childhood is most commonly caused by sarcomeric variants, with the β-myosin heavy chain ( MYH7 ) or myosin-binding protein C ( MYBPC3 ) genes most frequently implicated. 1,2 We have recently described the clinical presentation and outcomes of children with HCM caused by MYBPC3 variants and showed that these can cause early-onset disease with a high incidence of life-threatening arrhythmias, 3 contrasting with previous suggestions that they cause late-onset disease. 4…”
mentioning
confidence: 97%
See 1 more Smart Citation